Estudo do mecanismo molecular de transfecção mediada por ultrassom - De Paula, Daisy Maria Bentes [UNIFESP] (2010)
Ultrasound (US) has been widely used to improve the efficiency of non-viral vector transfection. However, the mechanism that enables the uptake of plasmid DNA in cells by US insonation is poorly understood, but it is typically attributed to sonoporation. Based on our previous results, we hypothesized that other mechanisms, such as endocytosis, are involved in this process. To explore the mechanism of plasmid DNA uptake, a plasmid vector expressing EGFP (pEGFP-N3: 4.7 kb) was used to transfect NIH3T3 cells using a therapeutic US without microbubbles and was monitored in real-time using a confocal microscope. We achieved about 40% transfection efficiency when we applied 2 W/cm2 with 20% of duty-cycle for 30 s, but 1 W/cm2 resulted in a very low level of transfection. In these experiments, the production of reactive oxygen species was augmented during the insonation but was stopped soon after turning off the US. Calcium influx was also augmented during the insonation, but its level did not return to basal levels following the 3-min observation period. However, 1 W/cm2 was not sufficient to mobilize calcium influx during the insonation, and calcium influx began 12 s after turning off the US. US insonation also changed the cell membrane potential to promote a hyperpolarization state, which returned to the normal state soon after turning off the US. The alteration of these parameters by US indicates the uptake of plasmid DNA by endocytosis. Finally, using a fluorescently labeled plasmid, we showed that this molecule enters into cells via clathrin-mediated endocytosis, not via caveolin-1.